Energetic electron precipitation associated with pulsating aurora: EISCAT and Van Allen Probe observations. Issue 4 (21st April 2015) - Miyoshi, Y.; Oyama, S.; Saito, S.; Kurita, S.; Fujiwara, H.; Kataoka, R.; Ebihara, Y.; Kletzing, C.; Reeves, G.; Santolik, O.; Clilverd, M.; Rodger, C. J.; et al.
Abstract Pulsating auroras show quasi‐periodic intensity modulations caused by the precipitation of energetic electrons of the order of tens of keV. It is expected theoretically that not only these electrons but also subrelativistic/relativistic electrons precipitate simultaneously into the ionosphere owing to whistler mode wave‐particle interactions. The height‐resolved electron density profile was observed with the European Incoherent Scatter (EISCAT) Tromsø VHF radar on 17 November 2012. Electron density enhancements were clearly identified at altitudes >68 km in association with the pulsating aurora, suggesting precipitation of electrons with a broadband energy range from 10 keV up to at least 200 keV. The riometer and network of subionospheric radio wave observations also showed the energetic electron precipitations during this period. During this period, the footprint of the Van Allen Probe‐A satellite was very close to Tromsø and the satellite observed rising tone emissions of the lower band chorus (LBC) waves near the equatorial plane. Considering the observed LBC waves and electrons, we conducted a computer simulation of the wave‐particle interactions. This showed simultaneous precipitation of electrons at both tens of keV and a few hundred keV, which is consistent with the energy spectrum estimated by the inversion method using the EISCAT observations. This result revealed that electrons with a wide energy range simultaneously precipitate into the ionosphere in association with the pulsating aurora, providing the evidence that pulsating auroras are caused by whistler chorus waves. We suggest that scattering by propagating whistler simultaneously causes both the precipitations of subrelativistic electrons and the pulsating aurora.